2020
DOI: 10.1093/mnras/staa2801
|View full text |Cite
|
Sign up to set email alerts
|

The R136 star cluster dissected with Hubble Space Telescope/STIS – II. Physical properties of the most massive stars in R136

Abstract: We present an optical analysis of 55 members of R136, the central cluster in the Tarantula Nebula of the Large Magellanic Cloud. Our sample was observed with STIS aboard the Hubble Space Telescope, is complete down to about 40 M⊙, and includes 7 very massive stars with masses over 100 M⊙. We performed a spectroscopic analysis to derive their physical properties. Using evolutionary models we find that the initial mass function (IMF) of massive stars in R136 is suggestive of being top-heavy with a power-law expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
160
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(183 citation statements)
references
References 114 publications
23
160
0
Order By: Relevance
“…They showed that if the measured IMF of the R136 young massive cluster is granted to be canonical, as observations indicate, then the true highmass IMF of R136 at its birth must be at least moderately top-heavy when corrected for the dynamical escape of massive stars. A top-heavy IMF in R136 is further supported by a direct star-counts analysis (Bestenlehner et al 2020).…”
Section: Observational Evidence For a Systematically Varying Imfmentioning
confidence: 66%
“…They showed that if the measured IMF of the R136 young massive cluster is granted to be canonical, as observations indicate, then the true highmass IMF of R136 at its birth must be at least moderately top-heavy when corrected for the dynamical escape of massive stars. A top-heavy IMF in R136 is further supported by a direct star-counts analysis (Bestenlehner et al 2020).…”
Section: Observational Evidence For a Systematically Varying Imfmentioning
confidence: 66%
“…The upper mass limit is motivated by the observation of very massive stars ( ∼ 100 − 300 M ) in young, massive star formation regions such as those identified in the Tarantula Nebula (e.g. Bestenlehner et al 2020). Adopting a different upper mass limit has a negligible effect on the low mass stellar population considered in this work.…”
Section: Bpassmentioning
confidence: 99%
“…The R136 star cluster in the 30 Dor region of the Large Magellanic Cloud (LMC) is a unique astrophysical laboratory; it is sufficiently young (1.5-2 Myr, de Koter et al 1998;Crowther et al 2016;Bestenlehner et al 2020) and rich (Crowther et al 2010) to allow the study of the formation and evolution of the most massive stars. Most of the information on R136 comes from Hubble Space Telescope (HST) observations, which was used to study various parameters including the cluster's star formation history, stellar content, and kinematics (Hunter et al 1995;Andersen et al 2009;De Marchi et al 2011;Cignoni et al 2015).…”
Section: Introductionmentioning
confidence: 99%